Metal-Based Radiopharmaceuticals in Inorganic Chemistry (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The field of radiopharmaceuticals is constantly evolving thanks to the great contributions of specialists coming from different disciplines such as inorganic chemistry, radiochemistry, organic and biochemistry, pharmacology, nuclear medicine, physics, etc. In particular, the use of radiometals has experienced a great increase as a result of the development of radionuclides production technologies. In this particular area, inorganic chemistry skills are mainly involved in developing target-specific radiopharmaceuticals based on radiometals for non-invasive disease detection and cancer radiotherapy.The Special Issue “Metal-Based Radiopharmaceuticals in Inorganic Chemistry” includes eleven research articles and one review. The production and applications of conventional and newly emerging research radiometals for diagnosis, therapy, and theranostics are the main focus of this Special Issue.